RAPID DEVELOPMENT OF STUDENTS' WRITING SKILLS IN GERMAN LANGUAGE - Gulnoza Eshniyozova Abdunazarovna (Scholar Express Journal, 2023)
This article talks about ways to teach students to write in English. It tells you what to look for in writing rules.
Keywords: Content and mechanism of teaching writing; teaching writing techniques; writing tasks and their types